PENGARUH LOYALITAS KERJA DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS SDM PADA PT. BPR ASHI MENGWI BADUNG - I Gede Arya Dwipayana; Ni Wayan Suartini; Ni Wayan Widani (Yayasan Nusantara Hasana Berdikari, 2023)
In achieving company goals, human resources have a very important role. Therefore, companies must always pay attention to employee job satisfaction and loyalty. Satisfied and loyal employees will make a major contribution to achieving company goals. This research aims to determine the effect of work loyalty and job satisfaction on HR productivity among PT employees. BPR ASHI. This research was structured descriptively using a quantitative approach method. In this research, the data collection instrument is a questionnaire to obtain information about a number of respondents representing a certain population and then statistical data analysis (SPSS) will be carried out to test the hypothesis that has been proposed. The results of this research were found from multiple linear regression analysis, it was concluded that work loyalty and job satisfaction had a positive effect on the HR productivity of PT employees. BPR ASHI. This means that increasing work loyalty and job satisfaction will significantly increase the HR productivity of PT employees. BPR ASHI. It is concluded that there is a significant partial influence of the work loyalty variable on HR productivity. Based on the results of the multiple linear regression test, it was found that the beta coefficient value for the work loyalty variable had a positive value of 0.489. There was a significant partial influence of the job satisfaction variable on HR productivity. Based on the results of the multiple linear regression test, it was found that the beta coefficient value for the job satisfaction variable had a positive value of 0.254 and there was a significant simultaneous influence of the Job Loyalty and Job Satisfaction variables on HR Productivity.